Predlog kvantitativnega modela vrednotenja geodiverzitete na primeru krasa Zgornje Pivke, Slovenija - Stepišnik, Uroš (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2016)
The article presents a new method for geodiversity evaluation, which was evaluated in the Upper Pivka karst area. The method is based on entire area evaluation on the basis of spatial distribution of geodiversity elements and terrain ruggedness. The method was developed for the purpose of objective and systematic geodiversity evaluation on various sites. In this article, we applied the method in the Upper Pivka area, where it demonstrated to be very useful.
Keywords: ecology; ekologija; geografski informacijski sistemi; geomorfologija; geomorphology; kras (geologija); krasoslovje; Pivka (reka); Slovenia; Slovenija